Paroxysmal Symptoms in Multiple Sclerosis—A Review of the Literature - Freiha, Joumana (J Clin Med, 2020)
Paroxysmal symptoms are well-recognized manifestations of multiple sclerosis (MS). These are characterized by multiple, brief, sudden onset, and stereotyped episodes. They manifest as motor, sensory, visual, brainstem, and autonomic symptoms. When occurring in the setting of an established MS, the diagnosis is relatively straightforward. Conversely, the diagnosis is significantly more challenging when they occur as the initial manifestation of MS. The aim of this review is to summarize the various forms of paroxysmal symptoms reported in MS, with emphasis on the clinical features, radiological findings and treatment options.